Odpowiedzi

2010-04-15T17:36:13+02:00
-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30 |:(-6)
x= -5

-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15 |-10
x=1,5

4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10 |:(-2)
x=-5
2010-04-15T17:37:51+02:00
-6(x+1)=24
-6X-6=24
-6x=6+24
-6x=30 |/(-6)
x=-5


-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-14-1
-10x=-15 |/(-10)
x=1,5


4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=4+6
-2x=10 |/(-2)
x=-5


Proszę bardzo:)
2010-04-15T17:38:17+02:00
-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30 /:(-6)
x=-5


-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15/:(-10)
x=³/₂
x=1½


4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10/:(-2)
x=-5